2013
DOI: 10.1364/ol.38.005040
|View full text |Cite
|
Sign up to set email alerts
|

Direct femtosecond pulse compression with miniature-sized Bragg cholesteric liquid crystal

Abstract: Direct compression of femtosecond optical pulses from a Ti:sapphire laser oscillator was realized with a cholesteric liquid crystal acting as a nonlinear 1D periodic Bragg grating. With a 6 μm thick sample, the pulse duration could be compressed from 100 to 48 fs. Coupled-mode equations for forward and backward waves were employed to simulate the dynamics therein, and good agreement between theory and experiment was obtained.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 21 publications
3
36
0
Order By: Relevance
“…(d) Nematic liquid crystals in nanostructured metamaterial [12]. their electro-optical counterparts that operate at milliseconds speed, several of these optically activated mechanisms can enable ultrafast all-optical switching operations in conjunction with sub-microseconds to nanoseconds and femtoseconds lasers [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. All-optical interactions and activation processes also do not require electrodes or complex circuitry, and can be mediated with a large degree of freedom in the direction and polarization states of the incident electromagnetic waves.…”
Section: F Figures 2(a)-(b)mentioning
confidence: 99%
See 3 more Smart Citations
“…(d) Nematic liquid crystals in nanostructured metamaterial [12]. their electro-optical counterparts that operate at milliseconds speed, several of these optically activated mechanisms can enable ultrafast all-optical switching operations in conjunction with sub-microseconds to nanoseconds and femtoseconds lasers [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. All-optical interactions and activation processes also do not require electrodes or complex circuitry, and can be mediated with a large degree of freedom in the direction and polarization states of the incident electromagnetic waves.…”
Section: F Figures 2(a)-(b)mentioning
confidence: 99%
“…In the next few sections, we shall discuss the fundamentals of these mechanisms and their dynamical characteristics, and explore the possibilities of utilizing them for fast responding all-optical switching and modulation operations. For completeness and possibly new applications, we also include a brief discussion of the ultrafast (femtoseconds) molecular electronic nonlinearities [49,[77][78][79][80][81][82][83][84][85] of NLC, as well as the isotropic (liquid) phase nanoseconds orientation nonlinearities [3,52,53].…”
Section: Mechanisms and Dynamics Of Laser Induced Refractive Index Ormentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that cholesteric liquid crystals (CLCs), which is a natural BG structure with refractive index modulation depth near 10 −1 [27], can be used to stretch and compress the fs pulses [28]. Importantly, a large nonlinear coefficient in the order of 10 −12 cm 2 /W with femtosecond response was reported in CLCs [27][28][29][30]. These findings open a new avenue to realize optical diode in femtosecond domain.…”
mentioning
confidence: 99%